Perencanaan Instalasi Pengolahan Air Limbah (IPAL) Portable Industri Laundry - Ramdhani, Ilham; Prio Utomo, Kiki; Widha Nugraheni, Putranty (Universitas Tanjungpura, 2026)
Laundry businesses provide significant benefits to the surrounding community's economy and can reduce unemployment and improve the community's standard of living. Based on monitoring data from the Environmental Agency (2018), there are 42 laundries in Pontianak City. One laundry business in Pontianak City without wastewater treatment is Kalesco Laundry. Wastewater from laundry activities is discharged directly into waterways without prior treatment. Laundry liquid waste has a high organic content, which means it can pollute the environment. The purpose of this planning is to design and calculate the budget for building a portable wastewater treatment system at the Kalesco laundry. Sampling was carried out using the grab sample method at 14.00 WIB, and the samples were then tested in the laboratory. The planned waste discharge is 4.15 m3 / day. Based on laboratory test results, the characteristics of the Kalesco laundry liquid waste were: TSS 205 mg/l, COD 1397 mg/l, BOD 608 mg/l, MBAS 3.81 mg/l, phosphate 0.160 mg/l, and pH 8.21. The result of this planning is the selected unit for portable wastewater treatment plant consisting of an equalization tank (0.2x0.1x1.5m), aerobic biofilter tank (1.4mx1.0mx1.5m), sedimentation tank (0.54mx0.27mx2m), and final storage tank (0.4mx0.2mx1.5m) with a total land area required of 2.50 m2 and a total cost of Rp. 4,999,55.